A Review of the Role of Social Cognition in Major Depressive Disorder - Weightman, Michael James; Air, Tracy Michele; Baune, Bernhard Theodor (Frontiers in Psychiatry, 2014)
Background: Social cognition – the ability to identify, perceive and interpret socially-relevant information – is an important skill that plays a significant role in successful interpersonal functioning. Social cognitive performance is recognised to be impaired in several psychiatric conditions, but the relationship with major depressive disorder is less well understood. The aim of this review is to characterise the current understanding of (i) the different domains of social cognition and a possible relationship with major depressive disorder, (ii) the clinical presentation of social cognition in acute and remitted depressive states, and (iii) the effect of severity of depression on social cognitive performance. Methods: Electronic databases were searched to identify clinical studies investigating social cognition in a major depressive disorder population, yielding 31 studies for this review. Results: Patients with major depressive disorder appear to interpret social cognitive stimuli differently to healthy controls: depressed individuals may interpret emotion through a mood-congruent bias and have difficulty with cognitive theory of mind tasks requiring interpretation of complex mental states. Social cognitive performance appears to be inversely associated with severity of depression, whilst the bias toward negative emotions persists even in remission. Some deficits may normalise following effective pharmacotherapy. Conclusions: The difficulties with social interaction observed in major depressive disorder may, at least in part, be due to an altered ability to correctly interpret emotional stimuli and mental states. These features seem to persist even in the remitted state, although some may respond to intervention. Further research is required in this area to better understand the functional impact of these findings and the way in which targeted therapy could aid depressed individuals with social interactions.